If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.04x + 0.07(1000 + -1x) = 660 0.04x + (1000 * 0.07 + -1x * 0.07) = 660 0.04x + (70 + -0.07x) = 660 Reorder the terms: 70 + 0.04x + -0.07x = 660 Combine like terms: 0.04x + -0.07x = -0.03x 70 + -0.03x = 660 Solving 70 + -0.03x = 660 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + -0.03x = 660 + -70 Combine like terms: 70 + -70 = 0 0 + -0.03x = 660 + -70 -0.03x = 660 + -70 Combine like terms: 660 + -70 = 590 -0.03x = 590 Divide each side by '-0.03'. x = -19666.66667 Simplifying x = -19666.66667
| 4b+20=60 | | F(x)=2ln(6-x)+3 | | -2m-5(1-5m)=110 | | 5+(x-9)+x=59 | | F(x)=xsq+x | | 2(x+12)+7(x-5)=4x-56 | | (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= | | -3(7+5n)=-96 | | -1/3(2b-6) | | 3+4x+3=-2 | | X(7x-3)=(7x+8)(x-1) | | 7(2x-3)=3+2(x+5)+7 | | 11(-9-2x)=-(12x+11) | | i+30=28 | | 4(-5+x)=48 | | 3x+8=(6-x) | | 2(x-16)-5(x-3)=18 | | 6[x-10]+8=26 | | 7z+17=6z+8 | | 16x+5=-37 | | (x+9)(x-3)=(x+1)(x+1) | | [n/10]=3 |